(untitled) (American Journal of Interdisciplinary Research and Development, 2025)
This article investigates the didactic foundations and the specific characteristics of music teaching, with particular emphasis on the critical role of school repertoire in shaping students’ musical culture. The research integrates theoretical analysis and empirical observation, focusing on modern educational paradigms, the evolving nature of didactics in the context of music education, and the multi-dimensional impact of repertoire selection on students’ aesthetic, cognitive, and socio-emotional development. The article addresses the philosophical, methodological, and practical dimensions of music pedagogy, critically examines the criteria for repertoire selection, and explores the dialectic relationship between curriculum content and the cultivation of musical taste, appreciation, and creativity in the school environment. The findings demonstrate that a thoughtfully curated school repertoire, aligned with both didactic principles and students’ developmental needs, is instrumental in nurturing a lifelong engagement with music, fostering cultural continuity, and supporting the holistic formation of musical culture among young learners.